Low muscle mass and sarcopenia: common and predictive of osteopenia in inflammatory bowel disease. Issue 9 (5th March 2015) - Bryant, R. V.; Ooi, S.; Schultz, C. G.; Goess, C.; Grafton, R.; Hughes, J.; Lim, A.; Bartholomeusz, F. D.; Andrews, J. M.
Summary Background Body composition is poorly studied in inflammatory bowel disease (IBD). Sarcopenia describes a loss of muscle mass and strength. Aim To assess the prevalence of low lean mass (LM), sarcopenia and associated morbidity in an adult IBD cohort. Methods Cross‐sectional data were gathered on pre‐menopausal 18‐ to 50‐year‐old patients with IBD. Whole‐body dual‐energy X‐ray absorptiometry, anthropometric assessment and grip strength were performed. Low LM was defined as ≥1 s.d. below the population mean for appendicular skeletal muscle index [ASMI (kg)/height (m)²], and sarcopenia as both ASMI and grip strength ≥1 s.d. below population mean. Multivariate regression analyses were performed. Results Of 137 participants (median age 31 years, BMI 24.8 kg/m2), 56% were male and 69% had Crohn's disease (CD). Low LM and sarcopenia were observed in 21% and 12% of patients, respectively, and osteopenia/osteoporosis in 38% of patients (mean lumbar spine t‐score −0.3 ± s.d. 1.1). Grip strength predicted low LM and sarcopenia better than did body mass index (BMI) (OR 4.8 vs. OR 0.7 for low‐LM, P < 0.05 both). Normal BMI was falsely reassuring in 72% and 76% of patients with low ASMI and sarcopenia, respectively. Low LM and sarcopenia (OR = 3.6, P = 0.03; OR = 6.3, P = 0.02; respectively), but not BMI nor fat mass, predicted osteopenia/osteoporosis. Conclusions Low lean mass and sarcopenia are common in patients with IBD, and important to recognise as they predict osteopenia/osteoporosis. Grip strength testing should be incorporated into routine clinical practice to detect low lean mass deficits, which may go unrecognised using BMI alone.